Pelaksanaan Program Kegiatan Pengelolaan program Penyakit Kronis Di Puskesmas Mendawai - Suharyatno, Suharyatno; Purwaningsih, Puji; Chaerijah, Zumrotul; Widodo, Gipta Galih (LPPM UNIKAL, 2024)
The Chronic Disease Management Program (Prolanis) is an integrated health service system that aims to address the negative impact of lifestyle habits on health. A study was conducted to describe the implementation of this program at the Mendawai Health Center.The study used secondary data and employed descriptive analytic methods.The results revealed that the majority of participants were between 46-65 years old, female, unemployed, and had a high school education. Most participants engaged in medical consultation, educational activities, and received SMS reminders. However, home visits were conducted for only 57.4% of participants, and while 53.7% of diabetes mellitus cases were controlled, 61.2% of hypertension cases were not. The study suggests that the Mendawai Health Center community should take certain actions, but the text does not specify what those actions are. Overall, the Prolanis program shows promise in managing chronic diseases, but there is room for improvement in controlling hypertension.Suggestions for the community around the Mendawai Health Center to actively use Prolanis activities to maintain their health, especially for early detection of diabetes mellitus and hypertension.